2017
DOI: 10.1016/j.ijid.2017.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Immune recognition surface construction of Mycobacterium tuberculosis epitope-specific antibody responses in tuberculosis patients identified by peptide microarrays

Abstract: These data reveal the heterogeneity of epitope-dependent humoral immune responses in TB patients, partly due to geographical setting. These findings expose a new avenue for mining clinically meaningful vaccine targets, diagnostic tools, and the development of immunotherapeutics in TB disease management or prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Further analysis indicated that 150 studies involved in the peptide or epitope for TB, including 76 studies in epitope screening and prediction, 45 studies in evaluating immunogenicity, 8 studies in peptide-based vaccine construction, and 21 studies in assessing vaccine efficacy in animal models (Figure 3B and Table S1). Among these 150 articles, we found that 14 teams had published at least 3 articles in these four areas of TB epitopes or peptides, including six studies on epitope screening and prediction (181)(182)(183)(184)(185)(186) and three studies on immunogenicity (187-189) from Pro. Markus J Maeurer's team; seven studies on epitope screening and prediction from Pro.…”
Section: Research Status Of Tb Peptide-based Vaccinesmentioning
confidence: 99%
“…Further analysis indicated that 150 studies involved in the peptide or epitope for TB, including 76 studies in epitope screening and prediction, 45 studies in evaluating immunogenicity, 8 studies in peptide-based vaccine construction, and 21 studies in assessing vaccine efficacy in animal models (Figure 3B and Table S1). Among these 150 articles, we found that 14 teams had published at least 3 articles in these four areas of TB epitopes or peptides, including six studies on epitope screening and prediction (181)(182)(183)(184)(185)(186) and three studies on immunogenicity (187-189) from Pro. Markus J Maeurer's team; seven studies on epitope screening and prediction from Pro.…”
Section: Research Status Of Tb Peptide-based Vaccinesmentioning
confidence: 99%
“…Using the modeled structures of each variant allowed the investigation of differential B-cell epitope predictions and demonstrated high variability in the number of predicted B-cell epitopes among PPE18 variants. This observation builds on work investigating heterogeneity of epitope recognition in MTBinfected individuals in different geographic regions (Valentini et al, 2017). These results are pertinent to novel vaccine development, as humoral immunity has gained increased interest in the battle against TB (Achkar et al, 2015;Niki et al, 2018).…”
Section: Discussionmentioning
confidence: 83%
“…The second study by Valentini et al used peptide arrays to dissect the epitope specific humoral immune responses across the entire M. tuberculosis protein molecules. 31 An interesting finding was that patients from South America recognized more peptides compared to patients from South Africa (both groups HIV-negative). 31 A study using peptide microarrays found that sera from patients with sarcoidosis and Löfgren's syndrome recognised 68 -78% M. tuberculosis peptides once again suggesting mycobacterial involvement in sarcoidosis.…”
Section: Immunological Studiesmentioning
confidence: 95%
“…31 An interesting finding was that patients from South America recognized more peptides compared to patients from South Africa (both groups HIV-negative). 31 A study using peptide microarrays found that sera from patients with sarcoidosis and Löfgren's syndrome recognised 68 -78% M. tuberculosis peptides once again suggesting mycobacterial involvement in sarcoidosis. 32 Using paleomicrobiology it is possible to study the evolution of MTBC over the past ten millennia and its association with human migration, providing new insight into the probable origin of the different MTBC bacterial lineages.…”
Section: Immunological Studiesmentioning
confidence: 95%